The storyteller - Starmer, Aaron, 1976- (Starmer, Aaron, 1976- Riverman trilogy, 2017)
Fourteen-year-old Keri Cleary's brother Alistair has stopped talking after he witnesses the shooting of Kyle Dwyer. As everyone worries about Alistair and wonders where Charlie Dwyer and Fiona Loomis are, Alistair begins telling his sister strange stories about a parallel world called Aquavania where he claims Charlie and Fiona are trapped. Keri is skeptical that her brother's stories are delusions until she realizes that Alistair's stories overlap with her own that she's been writing in her journal.